2017
DOI: 10.1007/s41465-017-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Electrical Stimulation as a Tool to Enhance Attention

Abstract: Attention is a fundamental cognitive process-without it, we would be helplessly adrift in an overload of sensory input. There is considerable interest in techniques that can be used to enhance attention, including transcranial electrical stimulation (tES). We present an overview of 52 studies that have paired attention tasks with tES, mostly in the form of transcranial direct current stimulation (tDCS). In particular, we discuss four aspects of attention that have been most extensively targeted to date: visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 117 publications
(105 reference statements)
2
41
0
Order By: Relevance
“…tDCS effects are generally subtle and might therefore surface only in a within-subject design which is more sensitive because it takes out individual variance in baseline task performance and the degree of vigilance decrement over time (although we tried to control for the first with the staircase procedure). However, compared to many tDCS studies that previously reported effects on attentional performance using a between-subjects design [39], our sample size was relatively large with 30 to 34 participants in each stimulation group. It should also be noted that the effects of tDCS in general are debated [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tDCS effects are generally subtle and might therefore surface only in a within-subject design which is more sensitive because it takes out individual variance in baseline task performance and the degree of vigilance decrement over time (although we tried to control for the first with the staircase procedure). However, compared to many tDCS studies that previously reported effects on attentional performance using a between-subjects design [39], our sample size was relatively large with 30 to 34 participants in each stimulation group. It should also be noted that the effects of tDCS in general are debated [42].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the effects of tDCS in general are debated [42]. As we pointed out in an earlier review, the wide range in stimulation parameters that is used in tDCS studies and individual differences in the effects of tDCS might contribute to the failure to find (consistent) effects [39]. Also, the neural effects of tDCS itself may be smaller than assumed, as it was recently shown that the strength of the electric field in the brain is at the lower bound for it to be physiologically effective [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Attention is a fundamental cognitive process; without it, people would helplessly adrift in an overload of sensory input [2]. The link between attention and stimulation has been widely accepted.…”
Section: B Fragmented Teaching Based On Classroom Attention 1) Invermentioning
confidence: 99%
“…One important aim of such studies is to causally link specific cognitive processes and behaviors to (changes in) the functioning of specific brain regions and networks in healthy human adults. Notably, extensive review studies have failed to reveal consistent and reproducible effects of tDCS on attentional functions (Reteig, Talsma, van Schouwenburg, & Slagter, ), working memory (Russowsky‐Brunoni & Vanderhasselt, ), or executive function, language, and memory (Horvath, Forte, & Carter, ). rTMS protocols seem to suffer less severely from such issues (e.g., Hsu, Ku, Zanto, & Gazzaley, ), but unexpected or null findings are frequently reported here as well (for review, see, e.g., Guse, Falkai, & Wobrock, ).…”
Section: Introductionmentioning
confidence: 99%